In Vitro Differentiation of Antifungal Effect in Herbal Toothpaste and Non Herbal Toothpaste against Candida albicans - Rafsyanjani, Elsa Candra; Riswiyanto, Risya Cilmiaty Arief; Haryati, Sri (Nexus Kedokteran Klinik, 2016)
Introduction: Beside sodium monofluorophosphate, herbal toothpaste contained betel leaf extracts and lime extracts which  were  active composition of toothpaste. This research aimed to know in vitro differentiation of antifungal effect in herbal toothpaste and non herbal toothpaste against Candida albicans. Methods: This study applied an analytical experimental method. The subject of this research were cultured Candida albicans and taken by purposive randomized sampling. Toothpastes used in this study were toothpaste with 1 herbal ingredient, toothpaste with 2 herbal ingredients and non-herbal toothpaste. This research used 16 treatment groups by giving toothpaste solution with concentration of 20%, 30%, 50%, 70% and 90%, and this was also given ketoconazole 25 µg/ml as positive control. Concentration expressed as weight per volume (w/v). This research was repeated three times to minimize the occurrence of bias. The plate was incubated at 37°C for 24 hours and then formed inhibitory diameter zone was measured. The data was analyzed using One-Way ANOVA test, then this was continued by Least Significant Differences (LSD) Post-Hoc test. Results: One-way ANOVA test showed that there were differences of antifungal effect in herbal toothpaste and non herbal toothpaste (p = 0.003). Compared to non-herbal toothpaste, toothpaste with 1 herbal ingredient had significant differences started in concentration of 70%. Toothpaste with 2 herbal ingredients had significant differences started in concentration of 50%. Meanwhile, toothpaste with 2 herbal ingredients had significant differences compared to toothpaste with 1 herbal ingredient started in concentration of 90%. Conclusions: The antifungal effect in both herbal toothpaste and non herbal toothpaste were different. However, the significant differences appeared significantly in different concentrations. Keywords: Antifungal effect, herbal toothpaste, non herbal toothpaste, Candida albicans